2022
DOI: 10.1088/2051-672x/ac849b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface quality and optimization of process parameters in laser-assisted cutting of SiC ceramics

Abstract: In order to improve the surface quality of laser-assisted turning silicon carbide (SiC) ceramics, the effects of laser power, rotational speed, cutting depth and feed speed on surface quality are investigated. Taking the surface roughness as the characterization value, the reasonable selection range of each factor is determined by the numerical simulation results of temperature field and the single factor experiment results; orthogonal experiments and range analysis are performed on laser power, rotational spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Chen Cao conducted research on SiC laser-assisted turning and found through experiments that plastic processing occurs when the laser power is 185-225 W. The minimum roughness obtained is 0.45 μm [23]. Di Dai used TM to study the influence of laser power, spindle speed, cutting depth and feed speed on the surface roughness of laser-assisted turning of SiC, and the surface roughness was reduced to 0.293 μm under the optimal combination of process parameters [24]. In recent years, LAM has also been gradually applied to single-point diamond turning.…”
Section: Introductionmentioning
confidence: 99%
“…Chen Cao conducted research on SiC laser-assisted turning and found through experiments that plastic processing occurs when the laser power is 185-225 W. The minimum roughness obtained is 0.45 μm [23]. Di Dai used TM to study the influence of laser power, spindle speed, cutting depth and feed speed on the surface roughness of laser-assisted turning of SiC, and the surface roughness was reduced to 0.293 μm under the optimal combination of process parameters [24]. In recent years, LAM has also been gradually applied to single-point diamond turning.…”
Section: Introductionmentioning
confidence: 99%
“…Porosity, also known as the void fraction, is a measure of the void or empty spaces that are present in a material. Porosity is calculated as a proportion of the volume of voids relative to the total volume of the material [15][16][17][18][19][20][21][22][23][24]. The corrosion behavior of AA8011-ZrB2 composites was investigated using an in situ approach, and the presence of ZrB2 was verified using XRD and EDS.…”
Section: Introductionmentioning
confidence: 99%